ICT pathways to poverty reduction empirical evidence from East and Southern Africa - Adera, Edith Ofwona (Practical Action Publishing, 2014)
This book provides new empirical evidence on access to and use of ICTs and their effect on poor households in four East African countries--Kenya, Rwanda, Tanzania, and Uganda--along with experiences from other countries in Southern Africa. ICT Pathways to Poverty Reduction presents a conceptual framework to analyze how poverty dynamics change over time and to shed light on whether ICT access benefits the poor as well as the not-so-poor. Overall, the study concludes that ICTs make a difference to the livelihoods of the poor and contribute to reducing both financial and non-financial dimensions of poverty. Information and communication technologies (ICTs) have been proven to promote economic growth, but do we know that ICTs can reduce poverty? This book addresses the questions: Under what conditions do women benefit economically from using ICTs? How are the livelihoods of rural users affected? Which ICTs are being used by low-income entrepreneurs? ICT Pathways to Poverty Reduction is essential reading for policymakers, researchers, and academics in international development or ICT for development, as well as staff of development agencies working on livelihoods for the poor.